Protecting the Land Tenure Rights of Papuan Indigenous Peoples After New Autonomy Region - Wicaksana Prakasa, Satria Unggul; R.S. Rakia, A. Sakti; Wook, Izawati (Indonesia Law Reform Journal, 2023)
The issues with indigenous peoples are very frequent, the impact of development, investment, and deforestation is accompanied by land conversion activities for oil palm plantations and mining, making the rights of indigenous peoples marginalized. In this context, this study seeks to investigate: (1). What problems are experienced by the Papuan Indigenous Peoples and what protection should be accepted by legal and human rights approaches? (2) What are the challenges of Special Autonomy in Papua following the stipulation of the latest Special Autonomy Law, especially in Southwest Papua, and what kind of projections and challenges are needed to protect the Papuan people at large? This research uses socio-legal methods to identify legal procedures related to socio-cultural and political-economic aspects of the Papuan community. The result of this study shows that several points are specified to protect Indigenous Peoples rights in Papua, especially after Special Autonomy, namely the importance of protecting the human rights of Indigenous Peoples related to the right to self-determination, recognition of adat rights, and basic rights that should have affirmative policies carried out by the state to ensure that Indigenous Peoples can play a major role in protecting the environment and contributing to climate change prevention. Investment or state authority must be limited to protect, promote, and respect Indigenous Peoples in Papua and also Southwest Papuans. Then, with regard to the DOB in Papua, of course, it must be returned to its noble goal of protecting the rights of the Papuan people in realizing welfare and independence. Abuse of various forms of authority, including special autonomy funds in Papua must be condemned and strictly processed. Abstrak Problematika terhadap masyarakat adat sangat sering terjadi, dampak pembangunan, investasi, deforestasi disertai dengan aktivitas alih-fungsi lahan untuk perkebunan kelapa sawit dan pertambangan, menjadikan hak-hak masyarakat hukum adat menjadi tersingkirkan. Pada konteks ini kita perlu mengidentifikasi lebih dalam: (1). Bagaimana  problematika yang dialami MHA Papua dan perlindungan yang harusnya diterima pendekatan hukum dan HAM; (2). Bagaimana tantangan Otsus Papua pasca UU Otsus terbaru, khususnya di Papua Barat Daya, proyeksi dan tantangan seperti apa yang dibutuhkan untuk melindungi masyarakat Papua secara luas. Penelitian ini menggunakan metode sosio-legal untuk mengidentifikasi prosedur hukum serta lebih dari itu berkaitan dengan aspek sosio-kultur, dan  politik-ekonomi masyarakat Papua. Hasil penelitian ini adalahsetidaknya ada beberapa point untuk melindungi hak MHA di Papua khususnya pasca Otsus, yaitu pentingnya melidungi hak asasi dari MHA, berkaitan dengan hak menentukan nasibnya sendiri, pengakuan terhadap hak ulayat, serta hak-hak dasar yang harusnya ada kebijakan afirmatif yang dilakukan oleh negara untuk meastikan bahwa MHA dapat menjalankan peran besarnya dalam melindungi lingkungan hidup serta berkontribusi terhadap pencegahan perubahan iklim. Atas nama investasi atau otoritas negara yang berlebih, harus dibatasi dalam rangka perlindungan, pemajuan, dan penghormatan terhadap MHA, khususnya MHA di Papua. Kemudian, berkaitan dengan DOB di Papua termasuk di Papua Barat Daya, tentu harus dikembalikan kepada tujuan mulianya untuk melindungi hak masyarakat Papua dalam mewujudkan kesejahteraan dan kemandirian.